Exploring radiation measurement after Fukushima: When media ecology meets citizen science - Yasuhito Abe (Mètode Science Studies Journal: Annual Review)
While various scholars have investigated the role of citizens in generating scientific data after the Fukushima Daiichi nuclear disaster under the labels of citizen science and citizen sensing, this essay draws on media ecology and explores its potential theoretical usefulness for enhancing our understanding of post-Fukushima citizen science practices. Taking Marshall McLuhan’s perspective of technology as a medium, this article creates a theoretical framework for foregrounding the role of a measurement device (of radiation levels, in this case) in extending its user’s body and mind. In doing so, this essay attempts to contribute to the fields of media studies and Science, Technology, and Society (STS).